"An inescapable network of mutuality": the conversation between Senghor's philosophy and King's vision in the "Elegy for Martin Luther King". Issue 3 (2nd September 2017) - Spleth, Janice
ABSTRACT: In 1979, Léopold Sédar Senghor published his last book of poetry, Élégies Majeures ( Major Elegies ), a work that includes a tribute to the great American Civil Rights leader Martin Luther King, Jr. The "Elegy for Martin Luther King" consists of five distinct parts set off by roman numerals. The first three parts of the poem, with their allusions to Africa, the French Revolution, colonization, independence, and both the domestic and international perils facing the new nation of Senegal, might seem at first glance to be a digression from the subject announced by the title, but a reading of the elegy as a dialogue between Senghor and King as two men of ideas and action, whose writing shares common themes and whose battles were informed by similar challenges, allows us to see the unity of the work through the many ways that the African-American humanist's principles are confirmed and illustrated in the imagination of the Senegalese poet.